Telomere Loops and Homologous Recombination-Dependent Telomeric Circles in a Kluyveromyces lactis Telomere Mutant Strain - Cesare, Anthony J. (American Society for Microbiology (ASM), 2008)
The Kluyveromyces lactis ter1-16T strain contains mutant telomeres that are poorly bound by Rap1, resulting in a telomere-uncapping phenotype and significant elongation of the telomeric DNA. The elongated telomeres of ter1-16T allowed the isolation and examination of native yeast telomeric DNA by electron microscopy. In the telomeric DNA isolated from ter1-16T, looped molecules were observed with the physical characteristics of telomere loops (t-loops) previously described in mammalian and plant cells. ter1-16T cells were also found to contain free circular telomeric DNA molecules (t-circles) ranging up to the size of an entire telomere. When the ter1-16T uncapping phenotype was repressed by overexpression of RAP1 or recombination was inhibited by deletion of rad52, the isolated telomeric DNA contained significantly fewer t-loops and t-circles. These results suggest that disruption of Rap1 results in elevated recombination at telomeres, leading to increased strand invasion of the 3′ overhang within t-loop junctions and resolution of the t-loop junctions into free t-circles.